The Oxford Handbook of Religion, Conflict, and Peacebuilding - Omer, Atalia ca. 20./21. Jh. (Oxford Handbooks, 2014)
This volume provides a comprehensive and interdisciplinary account of the scholarship on religion, conflict, and peacebuilding. Looking far beyond the traditional parameters of the field, the contributors engage deeply with the legacies of colonialism, missionary activism, secularism, orientalism, and liberalism as they relate to the discussion of religion, violence, and nonviolent transformation and resistance. Featuring numerous case studies from various contexts and traditions, the volume is organized thematically into five different parts. It begins with an up-to-date mapping of scholarshi